Creativity and Translation Quality: Opposing Enemies or Friendly Allies? - Rojo, Ana; Meseguer, Purificación (HERMES - Journal of Language and Communication in Business, 2018)
In recent years, placing the translator’s agency at the fore of creativity research has drawn the scholars’ attention towards the need to define the role of individual personality traits in creativity in the translation process. But many questions still remain as to the role that a creative personality may play in the translation process and the final quality of translation performance. The study proposed here specifically aims to investigate the consequences of a creative profile for translation performance. The experiment correlates the scores of forty Spanish professional translators on a validated creativity personality test with their scores on product indicators of creativity. Translations were rated for accuracy and creativity by two different examiners. Results of the study suggest that creative intelligence plays a role in guiding translational behaviour, directing the translator’s attention and fostering flexible thinking, but does not necessarily guarantee higher quality in terms of number of translation errors.